Problems of Cost Evaluation of Damage to Environmental Objects - G. G. Omel’yanyuk; M. A. Vakula; M. V. Nikulina (Теория и практика судебной экспертизы)
The article discusses the key issues of cost evaluation of damage to the environment. This is a problem of legislative regulation arising from the lack of clear criteria of harm materiality to environmental objects; the problem of regulation of the content of ecotoxicants in various environments; the problem of methodological support. The difficulties of determining the “initial” state of the violated environmental objects, as well as fundamental differences in approaches to the calculation of economic damage to environmental objects are also analysed. It is shown that a possible resolution for these issues is environmental forensics involving the application of specialized knowledge of natural sciences, ecology in particular, to specify the consequences of an environmental offence, causal relationship and economic damage to the environmental objects. Forensic environmental experts have integrated knowledge of natural sciences and law.